Manufacture and Compositional Analysis of Silicon Nitride Composites with Different Carbon Additions - Csaba Balazsi; Ferenc Weber; Zsolt Kasztovszky (Communications - Scientific letters of the University of Zilina, 2004)
Carbon black and graphite nano/micrograins and sintering additives (Al2O3 and Y2O3) were added to silicon nitride starting powder. These mixtures were mechanochemically activated several hours in a planetary type alumina ball-mill in order to achieve a homogenous mass. As an alternative to nano- and micrograins, carbon fibres were added to carbon free silicon nitride batches. After dry pressing of rectangular bars sinter-HIP was applied. Structural, morphological and compositional analyses were performed on as-prepared samples. Bending strength and elastic modulus were found to be influenced by amount of carbon black and graphite introduced in silicon nitride matrix.